Awareness and Perception of Basel - II Norms Across Indian Banks: An Empirical Study - Pandya, Bhavin U.; Prajapati, Kalpesh P. (Indian Journal of Finance, 2013)
To soar the new heights of excellence, the Indian Banking industry requires a combination of new technologies, better processes of credit and risk appraisal, treasury management, product diversification, internal control and external regulations. With respect to the changing scenario and roller coaster ride of the banking industry, the Reserve Bank of India announced guidelines for implementation of Basel-II norms for all banks and made it compulsory for all scheduled commercial banks to implement the Basel-II norms. Implementation of Basel II is seen as a topsy-turvy situation for banks and has created challenges in the sector in many jurisdictions. There is a need for bank employees to have sufficient understanding of the Basel-II accord in order to guide the banking growth rate in the positive direction. Lack of understanding among employees regarding the new Basel-II accord affects banks negatively as these are the basis for any banking action. The objective of this paper is to find out the awareness level, as well as the perception among bank employees about the Basel-II norms, and also examines the efforts made by them for implementing it in their banks.